Lanzavecchia mangrovi sp. n. (Nematoda, Dorylaimida) from mangroves of Red River Estuary, Vietnam. - Gagarin, Vladimir G. (Zootaxa, 2014)
A new nematode species found in the Red River Estuary of Vietnam is described. Lanzavecchia mangrovi sp. n. is morphologically close to L. coomansi Nicholas, Stewart, 1984, but differs in its longer body (L = 2.71–3.76 µm versus L = 2.2–2.9 µm), shorter spicules (63–65 mm versus 72–88), longer prerectum (500–675 mm versus 262–310 µm) and shorter distal portion of tail in relation to the proximal portion (0.6–0.8 versus 0.9–2.3).